2019
DOI: 10.9734/jpri/2019/v26i630153
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial Properties of Valeriana officinalis, Satureja bachtiarica and Thymus daenensis Methanolic Extracts against Helicobacter pylori

Abstract: Aims: Helicobacter pylori infection spreads widely in the world and has several complications including gastric cancer. The aim of this work is to investigate the antimicrobial properties of Valeriana officinalis L., Satureja bachtiarica and Thymus daenensis extracts against H. pylori. Methods: The disk diffusion test was used in this experiment. Methanolic extract was isolated from Valeriana officinalis L., Satureja bachtiarica and Thymus daenensis. Ten clinical isolates of H. pylori were used in this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Regarding therapeutic indications, it is advisable for people with nervous agitation, mild anxiety, and difficulties in sleeping [105,106]. There are also studies that demonstrate its antibacterial [107] and antimicrobial [108] properties. It is non-toxic, non-irritating, and can cause sensitisation.…”
Section: Essential Oils In Plantsmentioning
confidence: 99%
“…Regarding therapeutic indications, it is advisable for people with nervous agitation, mild anxiety, and difficulties in sleeping [105,106]. There are also studies that demonstrate its antibacterial [107] and antimicrobial [108] properties. It is non-toxic, non-irritating, and can cause sensitisation.…”
Section: Essential Oils In Plantsmentioning
confidence: 99%
“…(2017) [34] disclosed that the T. kotschyanus, T. vulgaris, and T. pubescens had the highest antibacterial effects amongst all examined thyme species. Antibacterial effects of diverse thymus species cultivated in Italy [38], Iran [39], Brazil [39], and Hungary [40] were reported in the literature. In keeping with this, further researches are required to assess the antibacterial effects of all types of the T. daenensis extract against diverse kinds of food-borne bacteria.…”
Section: Severalmentioning
confidence: 99%
“…Valerenic acid can be used to in different disorders such as depression, chronic anxiety, and sleep disorders on the basis of previous studies [4]. Based on previous literatures, the valerenic acid component had antimicrobial effects on different microorganisms such as Helicobacter pylori, Staphylococcus aureus and Candida albicans and its methanolic extract functions were dose-dependent [6][7][8]. Since the antimicrobial activity of V. officinalis in the total extract was correlated with abundant monoterpenoids and sesquiterpenoids, more research on various aspects of pharmaceutical effects is suggested.…”
Section: Dear Editormentioning
confidence: 99%